(untitled) - Schmid, Rolf D. (Berlin,New York, 1991)
"Biotechnology in Japan" is a guide to the economic, scientific and regulatory aspects of Japanese research centres and companies. Profiles for more than 400 private Japanese companies and almost 200 universities and research institutes are given in detail. Ministries providing research guidelines and ongoing research projects are detailed. This reference book on biotechnology is intended for consultants, managers and scientists and administrators in international scientific and technological exchange programmes
Keywords: Biotechnology,Biotechnology; Government policy; Japan,Japan